2017
DOI: 10.1007/s00404-017-4511-9
|View full text |Cite
|
Sign up to set email alerts
|

The preoperative albumin level is an independent prognostic factor for optimally debulked epithelial ovarian cancer

Abstract: The preoperative albumin level is an independent prognostic factor for overall survival in optimally debulked EOC patients. Further investigations about preoperative albumin level in prognostic models will contribute to the literature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(46 citation statements)
references
References 37 publications
2
42
0
2
Order By: Relevance
“…After screening the titles and abstracts, 23 articles qualified for a full-text review ( Figure 1 ). Finally, 12 cohort studies 8 , 12 21 , 36 were included in the present analysis.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…After screening the titles and abstracts, 23 articles qualified for a full-text review ( Figure 1 ). Finally, 12 cohort studies 8 , 12 21 , 36 were included in the present analysis.…”
Section: Resultsmentioning
confidence: 99%
“…Most (7/12, 58.3%) of the included studies were conducted in Europe, 8 , 15 , 16 , 18 , 20 22 while 4/12 (33.3%) were conducted in Asia, 12 14 , 17 and 1/12 (8.3%) was conducted in the USA. 19 Serum albumin was a categorical variable in 9/12 (75.0%) studies 8 , 12 , 14 19 , 21 and a continuous variable in 3/12 (25.0%) studies. 13 , 20 , 22 …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In our study, we found that the level of albumin was elevated after the course of NACT (37.47 ± 5.42 vs 42.61 ± 3.46, P 0.05). Cancer patients have low preoperative albumin levels, especially those with advanced-stage disease and patients with ascites 16 ; the mechanisms for this low level involve a decrease in amino acid intake and albumin synthesis 17 as well as an increase in albumin leakage to the extravascular space in patients with ascites. There were 21 (80.77%) patients with massive ascites upon diagnosis, and the largest mean diameter of the ascites assessed by ultrasound was 104.05 ± 31.75 mm.…”
Section: Discussionmentioning
confidence: 99%